Glucose Control during a Driving Training in Patients with Type 1 and Type 2 Diabetes Mellitus – a Randomised, Controlled Trial - Truninger, R.; Uthoff, H.; Capraro, J.; Frauchiger, B.; Spinas, G. A.; Wiesli, P. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To investigate the effect of prolonged acute mental stress by means of a driving training on glucose control in patients with type 1 and type 2 diabetes mellitus.39 patients with insulin-treated diabetes (18 type 1, 21 type 2 diabetes) were exposed to mental stress by means of a 2 h-driving training. The training session started 15 min after intake of a standard meal. Blood glucose, blood pressure, heart rate, salivary cortisol, and subjective stress perception were monitored in regular intervals and compared to a control day.On the stress testing day, blood pressure rose from 142/86±16/9 mmHg to 162/95±22/11 mmHg (p<0.001), heart rate from 72±11 bpm to 86±16 bpm (p<0.001) and subjective stress perception from 1.4±0.6 to 4.7±2.5 points (p<0.001). Salivary cortisol concentrations increased from a median of 5.1 nmol/l (Interquartile Range (IQR) 3.5–7.5 nmol/l) at baseline to 7.7 nmol/l (IQR 4.7–12.8 nmol/l, p<0.001), all these measurements remained stable on the control day. Glucose control showed no significant difference on the stress testing day compared to the control day (mean difference over time=0.22 mmol/l, 95%-CI −1.5 to +1.9 mmol/l, p=0.794). A multivariate linear regression and correlation analysis showed no association of demographic characteristics (diabetes type, age, body mass index (BMI), diabetes duration, HbA1c), objective or subjective stress parameters with the course of glucose concentrations during the driving training.Although a 2 h-driving training causes increased subjective and objective stress parameters, glucose control is maintained in patients with insulin-treated diabetes.
Keywords: acute mental stress; catecholamines; salivary cortisol; hypothalamo-pituitary adrenal axis; insulin resistance